SISTEM INFORMASI DETEKSI KEHADIRAN DAN MEDIA PENYAMPAIAN PENGUMUMAN DOSEN DENGAN MENGGUNAKAN TEKNIK PENGENALAN QR CODE - O.K Saddam Hussein; Refni Wahyuni; Harun Mukhtar (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2018)
“Information Systems of Attendance Detection and Media Submission of Lecturer Announcement by Using Engineering Introduction QR Code "is an application that serves to support the process of disseminating information on the campus of Muhammadiyah University of Riau to become more effective and efficient and facilitate students in obtaining information. This application can be used by Lecturers and Students as recipient of information. The results of this study is a web-based application that can support the process of disseminating information on the campus of the University of Muhammadiyah Riau. The research was built using the Waterfall software development method, using UML to document, specify, and model the system. Implemented using PHP programming language using Laravel Framework and using MySQL database and other supporting software.